2019
DOI: 10.1177/0255761419873782
|View full text |Cite
|
Sign up to set email alerts
|

Intrapersonal skills and music performance in elementary piano students in Spanish conservatories: Three case studies

Abstract: This study is based on the premise that emotional skills—comprised of an intrapersonal dimension and an interpersonal dimension—help to achieve personal balance, which in turn can enhance performance. Following from this premise, the improvement of music students’ emotional skills might have a positive effect on their musical performance. The recognized relationship between music and emotion therefore suggests that music education is a suitable context for developing emotional skills. The article examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Improving emotional skills can improve the results of music practice. A research study addressed the relationship between emotional skills and instrumental piano practice [ 80 ], obtained several results. Firstly, they found that identifying emotions helped students to integrate emotional expression into their piano playing and to play more fluently.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improving emotional skills can improve the results of music practice. A research study addressed the relationship between emotional skills and instrumental piano practice [ 80 ], obtained several results. Firstly, they found that identifying emotions helped students to integrate emotional expression into their piano playing and to play more fluently.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies used musical training as the independent variable and obtained evidence that it improved diverse socio-emotional competencies, including: identifying emotions in images and/or texts [ 68 ]; a greater capacity to regulate emotions [ 63 ]; concentration and creativity [ 82 ]; students’ ability to recognise emotions [ 73 ]; improved learning and mathematics [ 76 ]; a positive effect on children’s self-expression, self-efficacy, and social skills [ 78 ]; improved the feelings experienced when attending class [ 69 ]; greater emotional awareness and motivation from singing [ 66 ]; increased empathy and positive feelings for learning [ 67 ]; influenced the effects of emotional understanding [ 64 ]; influenced emotional awareness, regulation and autonomy [ 80 ]; increased pro-social behavior in neurotypical children in relation to the social exclusion of autistic children [ 74 ]; promoted the development of pro-social skills [ 81 ]; improved behaviors such as anxiety, depression, post-traumatic stress disorder, inattention and some defiant attitudes [ 83 ]; and increased children’s motivation and thus their learning capacity [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is based on an extended causal convolutional neural network (DC-CNN), and the reduction features are introduced by controlling the gate activation unit of each neuron in the neural network to achieve the reduction of electronic artifacts. The DC-CNN adopted in the model exists in causal convolution and expanded convolution, and the DC-CNN has achieved good results in the speech synthesis model WaveNet [ 25 , 26 ].…”
Section: Dc-cnn-based Music Notation Recognition Modelmentioning
confidence: 99%
“…e characteristics of the piano music are used to process the filter samples, and the piano music is separated according to the frame. In order to blindly process the cell matching, the hidden Markov model can be used to smooth the signal transmission between adjacent frames of the piano music [15]. e multimedia recognition system based on the hidden Markov model to play music on the piano automatically selects the window function form according to the characteristics of the music played by the user on the piano.…”
Section: 3mentioning
confidence: 99%